FACTORS AFFECTING EMPLOYEE JOB SATISFACTION AT THE REPRESENTATIVE OFFICE OF THE POPULATION AGENCY NATIONAL FAMILY PLANNING (BKKBN) - Adhan, Muhammad; Afriyani, Mery; Azhar, M. Elfi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
The problem in this study is how the effect of work conflict, work environment and work stress on employee job satisfaction at the Representative Office of the Population and Family Planning Agency (BKKBN) North Sumatra. This study aims to determine partially the variables of work conflict, work environment and work stress affect employee job satisfaction and the effect of work conflict, work environment, and job stress simultaneously on employee job satisfaction. associative and quantitative. The sampling technique used a saturated sample to 84 permanent employees. The data collection technique used interviews, documentation studies and questionnaires. The data analysis technique of this research uses classical assumption test and multiple linear regression analysis. Data processing in this study used statistical software SPPS 20. The results showed that based on the results of the t test, the conflict variable partially had a negative and insignificant effect on job satisfaction. The work environment variable partially has a positive and significant effect on employee job satisfaction. Job stress variable has a positive and insignificant effect on employee job satisfaction. In the results of the f test in this study, simultaneously the variables of work conflict, work environment and work stress have an effect on employee job satisfaction. The results showed that based on the results of the t test, the conflict variable partially had a negative and insignificant effect on job satisfaction. The work environment variable partially has a positive and significant effect on employee job satisfaction. Job stress variable has a positive and insignificant effect on employee job satisfaction. In the results of the f test in this study, simultaneously the variables of work conflict, work environment and work stress have an effect on employee job satisfaction. The results showed that based on the results of the t test, the conflict variable partially had a negative and insignificant effect on job satisfaction. The work environment variable partially has a positive and significant effect on employee job satisfaction. Job stress variable has a positive and insignificant effect on employee job satisfaction. In the results of the f test in this study, simultaneously the variables of work conflict, work environment and work stress have an effect on employee job satisfaction.